Branhamella (Neisseria) catarrhalis: criteria for laboratory identification. - Doern, G V (1980)
Eleven clinically significant isolates of Branhamella catarrhalis grew well on modified Thayer-Martin medium and produced beta-lactamase, but did not grow on nutrient agar at 22 degrees C. Minimum inhibitory concentrations of vancomycin, colistin, and trimethoprim were found to be higher than the concentrations of these antibiotics in modified Thayer-Martin medium. The criteria necessary for laboratory identification of B. catarrhalis are discussed.